MTIF2 impairs 5 fluorouracil-mediated immunogenic cell death in hepatocellular carcinoma in vivo: Molecular mechanisms and therapeutic significance. (January 2021) - Xu, Dafeng; Wang, Yu; Wu, Jincai; Zhang, Zhensheng; Chen, Jiacheng; Xie, Mingwei; Tang, Rong; Cheng, Chen; Chen, Liang; Lin, Shiyun; Luo, Xiangxiang; Zheng, Jinfang
Graphical abstract: Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related morbidity and mortality; it has been reported that immune cell infiltration is a prognosis factor. Here we identified genes that associated with tumor immune cell infiltrate; the underlying mechanism was verified by in vivo and in vitro experiment. In this study, Weighted correlation network analysis (WGCNA) and CIBERSORT tool were used to identify MTIF2 as the hub tumor immune infiltrating gene in HCC. To investigate the underlying role played by MTIF2, MTIF2 was knocked down by transfection of shRNA targeting MTIF2, CCK8, and EdU incorporation assay was used to evaluate the effect of MTIF2 on proliferation, wound heal assay and transwell assay was used to confirm its effect on cell migration. Ecto-calreticulin on the cell surface was evaluated by flow cytometry, ATP, and HMGB1 secretion were tested to the investigated effect of MTIF2 on the immunogenic cell death (ICD) process. We found that down-regulation of MTIF2 impaired proliferation and migration capacity of HCC cells, chemoresistance to 5-Fluorouracil (5-FU) weakened after MTIF2 was knocked down. Reduced release of damage-associated molecular patterns (DAMP) was observed after MTIF2 was overexpressed, which subsequently impaired dendritic cell (DC) maturation and proliferation of CD8 + T cells. Mechanically, the co-IP experiment confirmed that MTIF2 could interact with AIFM1, prevents AIFM1 induced transcription of caspase3, and finally suppress apoptosis. In vivo experiment also used to confirm our previously conclusion, our result indicated that MTIF2 overexpression suppresses tumor apoptosis and immune cell activity in the 5-FU therapy in vivo model, by suppression maturation of tumor-infiltrated DC. Collectively, our study confirmed that MTIF2 impair drug-induced immunogenic cell death in hepatocellular carcinoma cells.